If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (x + -5) + (x + 62) = 180 Reorder the terms: x + (-5 + x) + (x + 62) = 180 Remove parenthesis around (-5 + x) x + -5 + x + (x + 62) = 180 Reorder the terms: x + -5 + x + (62 + x) = 180 Remove parenthesis around (62 + x) x + -5 + x + 62 + x = 180 Reorder the terms: -5 + 62 + x + x + x = 180 Combine like terms: -5 + 62 = 57 57 + x + x + x = 180 Combine like terms: x + x = 2x 57 + 2x + x = 180 Combine like terms: 2x + x = 3x 57 + 3x = 180 Solving 57 + 3x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-57' to each side of the equation. 57 + -57 + 3x = 180 + -57 Combine like terms: 57 + -57 = 0 0 + 3x = 180 + -57 3x = 180 + -57 Combine like terms: 180 + -57 = 123 3x = 123 Divide each side by '3'. x = 41 Simplifying x = 41
| 7x+10=15x+42 | | 30=4x-12/4 | | 4+5c=64 | | 7x+14-3x-12-x=2x+10+46 | | x+(x+95)+(x+25)=180 | | 15x-4=10x-9 | | x^6-6x+7=7 | | 2x-3=2y-9 | | (20.75)*5= | | 4n-5=59 | | X+10=x-55+x-15 | | 11=10+u | | 0=x-x^2 | | 8h-5=11 | | 2x-3+2y-9+y-1+2y-9=360 | | (6x-x^2)/2=0 | | 0.05+1.02x= | | 8-6y=26 | | 3m+3=2m+10 | | b/3-6=82 | | 3x+x=450 | | 6x-20=x+10+3x+10 | | 9p+4p-3p+2p-6=-5p-6 | | 12+(-7)+3(-8)= | | log(x^2-5x)=0 | | 3x+3=5x+21 | | 10x-10x=9x+8 | | x/7*x=2x | | (6x-x^2)/2 | | 5=2+3r | | 3w=96 | | 6x-x^2/2 |